Clinical Outcomes of Lung Cancer Patients After Lobectomy Surgery Using Thoracotomy and VATS Methods at Persahabatan Hospital from 2021 to 2024 - Aqilah Nurahmah Argani; Yanto Sandy Tjang; Feda Anisah Makkiyah; Muttia Amalia; Erlang Samoedro (CV. Inara, 2026)
Lobectomy is the primary surgical treatment for lung cancer and can be performed using thoracotomy or video-assisted thoracoscopic surgery (VATS). This study aimed to describe patient characteristics, preoperative clinical conditions, intraoperative findings, and postoperative outcomes of lung cancer patients undergoing lobectomy using both techniques at Persahabatan General Hospital from 2021 to 2024. A retrospective descriptive cohort study was conducted involving 49 patients, consisting of thoracotomy (n=35) and VATS (n=14). Data included demographic characteristics, comorbidities, lung function, cancer type, intraoperative variables, and postoperative outcomes, which were analyzed descriptively. The mean age was 50 ± 12.2 years with a median of 54 years, and most patients were in late adulthood. Males predominated in the thoracotomy group, while females were more common in the VATS group. Smoking history was frequent, whereas diabetes mellitus and COPD were only found in the thoracotomy group. Most patients had normal preoperative lung function and primary lung cancer, although lung metastases were more common in thoracotomy cases. Thoracotomy was more frequently associated with longer operative time (>3 hours), greater intraoperative blood loss, and higher need for blood transfusion compared to VATS, which more often had shorter operative duration (≤3 hours). Postoperative morbidity was low in both groups, and mortality was similar at 2%. Length of hospital stay was generally shorter in the VATS group compared to thoracotomy. In conclusion, thoracotomy is more often used in complex cases, while VATS offers advantages in selected patients, particularly in terms of operative efficiency and recovery, supporting individualized surgical decision-making.